2020
DOI: 10.1039/c9sc05403k
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional lanthanide coordination polymer nanosheets for detection of FOX-7

Abstract: A new class of luminescent lanthanide 2D nanosheets for detection of FOX-7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 49 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…One thing to note is the fast‐growing metal organic frameworks (MOFs), which are designed from the perspective of molecules, making full use of the high stability of metal units and versatility of organic linkers, have attracted more and more attention for their potential applications in the fields of adsorption and separation, [ 4–10 ] electrode and photoelectric materials, [ 11–17 ] sensing and detection, [ 18–31 ] catalysis and photocatalysis. [ 32–34 ] Compared with other sensors, such as the conjugated organic probes, nanomaterials, carbon dots, oligomers, the luminescent metal–organic frameworks (LMOFs) possess obvious advantages of enormous structural diversity, adjustable pore size, large surface areas, readily function groups assisted analyte binding, and purposefully implanted active sites, render those LMOFs with the greatest potential as the sensory materials in detecting the POPs.…”
Section: Introductionmentioning
confidence: 99%
“…One thing to note is the fast‐growing metal organic frameworks (MOFs), which are designed from the perspective of molecules, making full use of the high stability of metal units and versatility of organic linkers, have attracted more and more attention for their potential applications in the fields of adsorption and separation, [ 4–10 ] electrode and photoelectric materials, [ 11–17 ] sensing and detection, [ 18–31 ] catalysis and photocatalysis. [ 32–34 ] Compared with other sensors, such as the conjugated organic probes, nanomaterials, carbon dots, oligomers, the luminescent metal–organic frameworks (LMOFs) possess obvious advantages of enormous structural diversity, adjustable pore size, large surface areas, readily function groups assisted analyte binding, and purposefully implanted active sites, render those LMOFs with the greatest potential as the sensory materials in detecting the POPs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental results have shown that Tb-MOF has an excellent fluorescence response to phosphate ions (strong quenching effect on Tb 3+ emission). 32 Therefore, we intend to verify the feasibility of this phosphate reaction pathway in the ALP activity assay (Figure S4). The best candidate MOF was selected from the two dual-emission Tb-MOFs according to the response effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The dual-emission Ln-MOFs reported thus far include single-ligand, single-Ln 3+ MOFs, emissive guest-doped and dual-ligand Ln-MOFs, dual-lanthanide ion MOFs, and mixed Ln-MOFs with different emissions . Among them, the emissive guest-doped Ln-MOFs is likely to be faced with the leakage of guest molecules, the dual-ligand MOF design strategy is limited by the high blindness and high cost of dual ligand selection, the dual-lanthanide ion MOFs may have a poor anti-interference ability because many substances show similar effect on lanthanide ions, and mixed Ln-MOF systems may face the low mixing uniformity problem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their graphene-like geometric shape and enhanced surface area, along with their flexible nature, lightweight, and adaptable nature, make them an important class of materials for designing efficient SSEs. [32][33][34][35] Despite its significance, the systematic design approach of ARTICLE Please do not adjust margins Please do not adjust margins monomers and convenient methods to prepare SONs is scarce in the literature. Subsequently, attaining the desired SONs through the self-assembly process is a challenging issue owing to the associated intricacy in governing multiple noncovalent interactions in changing environment.…”
Section: Introductionmentioning
confidence: 99%